Quantitative magnetic resonance imaging in geriatric depression and primary degenerative dementia - Pantel, Johannes; Schröder, Johannes; Essig, Marco; Popp, Doris; Dech, Heike; Knopp, Michael V.; Schad, Lothar R.; Eysenbach, Katrin; Backenstraß, Matthias; Friedlinger, Michael (Journal of affective disorders, 1997)
Quantitative magnetic resonance imaging (MRI) was used to investigate volumes of different brain structures in 19 patients with late-onset major depression (DSM-III-R), 27 patients with Alzheimer's disease (NINCDS-ADRDA criteria) and 13 age matched controls. 3-D MRI sequences were acquired using a Siemens 1.5 T scanner. Whole brain volume, CSF volume, volume of the frontal and temporal lobes and the volume of the amygdala-hippocampus complex were assessed using the software NMRWin. Compared to the controls, depressed patients showed a significantly lower whole brain volume and a significantly higher CSF volume, whereas volumes of the frontal and temporal lobes as well as the amygdala-hippocampus complex volumes were not significantly decreased. In addition, depressed patients exhibited a higher ventricle-brain ratio suggesting a higher degree of central atrophy compared to healthy individuals. In contrast, Alzheimer patients showed significantly lower volumes than depressed patients and controls with respect to all volumetric parameters. Although the findings indicate the presence of brain atrophy in patients with late-onset depression, the pattern of volumetric changes in these patients differs markedly from that observed in patients with primary degenerative dementia.